Wozu Tiere? Il Mondo, l’Aperto, l’Essere tra Rilke e Heidegger - Gurisatti, Giovanni (Scenari, 2021)
Heidegger criticizes the “humanistic” subjectivity of the metaphysical tradition by arguing against its anthropocentric constitution. However, he does not share the idea – which can be found in Rilke – that such criticism should move in the anti-humanistic (anti-anthropocentric) direction of a zoo-biocentrism, which has in animal life its reference point. According to Heidegger, the critique of the anthropocentric subjectivity should instead move in the opposite direction, i. e. in the ultra-humanistic direction of an onto-heterocentrism, which, on the one hand, goes beyond (ultra: “beyond”) the anthropocentric humanism, but, on the other, proves to be even more radically (ultra: “even more”) human, in the sense of a humanity which finds in animal life its term of comparison, albeit a negative term.